Biopharmaceutical Characterization and Stability of Nabumetone–Cyclodextrins Complexes Prepared by Grinding - David Klarić; Željka Soldin; Anna Vincze; Rita Szolláth; György Tibor Balogh; Mario Jug; Nives Galić (Pharmaceutics)
Background: Nabumetone (NAB) is a poorly soluble nonsteroidal anti-inflammatory prodrug (BCS class II drug) whose solubility is significantly improved by complexation with cyclodextrins (CDs). Methods: The solid complexes, in a 1:1 molar ratio, were prepared by mechanochemical activation by grinding, using β-cyclodextrin (β-CD) and its derivatives, hydroxypropyl- and sulfobutylether-β-cyclodextrin (HP-β-CD and SBE-β-CD). The complexation was confirmed by differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and attenuated total reflectance Fourier-transformed infrared spectroscopy (ATR–FTIR). Obtained products were further characterized regarding their solubility, in vitro dissolution, permeability and chemical stability. Results: Co-grinding with HP-β-CD and SBE-β-CD yielded products that showed in vitro dissolution profiles in hydrochloric acid medium (pH 1.2) that were substantially different from that of pure NAB, yielding dissolution efficiency enhancements of 34.86 ± 1.64 and 58.30 ± 0.28 times, respectively, for the optimized products. Their in vitro dissolution and gastrointestinal permeability were also studied in a low-volume environment at pH 6.8, corresponding to the intestinal environment. Both β-CD derivatives increased NAB dissolution rate and NAB mass transport across the biomimetic membrane. The effect of β-CD derivatives on NAB chemical stability was studied under the stress conditions by the developed and validated UHPLC–DAD–HRMS method. In acidic conditions, pure and complexed NAB was prone to hydrolytic degradation, yielding one degradation product—pharmacologically inactive NAB metabolite. However, under the oxidative conditions at elevated temperatures, 10 NAB degradation products were identified from co-ground samples. All systems were stable during photo- and long-term stability studies. Conclusions: NAB complexes with HP-β-CD and SBE-β-CD are promising candidates for pharmaceutical product development.